FEATURES OF REGULATION OF ERYTHROPOIESIS IN PATIENTS WITH CHRONIC KIDNEY DISEASE STAGE 5D - E. S. Lapina; M. M. Batjushin; R. A. Belovolova; I. V. Sarvilina; V. N. Poganeva (Архивъ внутренней медицины)
The aim: to study features of the cytokine profile in patients with chronic kidney disease receiving treatment by programmed hemodialysis. Materials and methods: the study included 100 patients aged 53,4 ± 15,8 years with chronic kidney disease stage 5D, receiving hemodialysis. All patients were performed a detailed interview to clarify the clinical and anamnestic data, features of pharmacotherapy, physical examination, and complex laboratory research, which included hemogram, biochemical analysis of blood to definition of parameters of kidney function, protein, electrolytes, minerals and iron metabolism, determining the level of interleukin-3 and interleukin-6. Results: anemia was found in 89% of patients, had a normocytic normochromic character with elements of anisocytosis. The most severe anemia was associated with a lower dose of erythropoietin and iron, used in the last month. Interleukin-3 averaged 32,8 ± 8,3 pg / ml, minimum 15 pg / ml, maximum 56 pg / ml, which exceeded reference limits. When comparing the levels of interleukin-3 and erythropoietin dose differing vectors of these parameters in patients with anemia of varying severity were indicated. The correlations between the level of interleukin-3 and the fluctuation of the dose of erythropoietin in the last year (r = 0,54; p = 0,01) in patients with mild anemia, and the level of soluble transferrin receptor (r = 0, 84; p = 0,04) in patients with severe anemia were found. The level of interleukin-6 was also higher than the reference values and amounted to 64,6 ± 8,7 pg / ml, the lowest — 36,0 pg / ml, the most — 86,0 pg / ml. The patients with a high risk of systemic inflammation on the scale of Glasgow Prognostic Score had lower levels of interleukin-6. Conclusions: high levels of interleukin-3 and interleukin-6 were revealed in all patients identified. Inverse relationship of interleukin-3 and dose of erythropoietin in depend of severity of anemia was shown. The high risk of systemic inflammation associated with a lower concentration of interleukin-6, which does not allow its use as a universal marker of inflammation in patients with chronic kidney disease receiving hemodialysis.